The Effect of Shade and Harvest Age on Biomass and Patchouli Oil Production in the Lowlands - Riti, Dominggus Ngongo; Kurniawati, Ani; Nurcholis, Waras (Department of Agronomy and Horticulture, IPB University, 2025)
This study investigated the effects of different shade levels and harvest ages on the growth, biomass yield, and essential oil production of the patchouli (Pogostemon cablin Benth.) cultivar Sidikalang, cultivated in a lowland environment. The experiment was conducted in Bogor from August 2023 to February 2024, using a nested design with three shade treatments (no shade, 55%, and 75%) and three harvest ages (4, 5, and 6 months). The results indicated that 75% shade significantly enhanced vegetative growth, including plant height, number of secondary branches, and leaf production, suggesting that this level of shading is beneficial for patchouli cultivation in lowland areas. However, these effects were not significantly different from those observed under 55% shade. The highest essential oil yields were obtained from patchouli plants grown under 75% shade and harvested at 4 months, as well as from those grown under full sunlight and harvested at 6 months.